Trigonella Foenum-Graecum Seeds Lowers Postprandial Blood Glucose in Overweight and Obese Individuals - Sathyasurya, Daniel Robert; Ismail, Aziz Al-Safi; Wan Ishak, Wan Rosli (Hindawi Publishing Corporation, 2014)
This study determined the effects of fenugreek on postprandial plasma glucose (PPG) and satiety among overweight and obese individuals. Fourteen subjects were studied in the morning after overnight fasts on four separate occasions. Glycaemic responses elicited by 50 g carbohydrate portions of white bread and jam with or without 5.5 g of fenugreek and fried rice with or without 5.5 g fenugreek were determined over 2 h. The primary endpoint was the incremental area under the plasma glucose response curve (IAUC). Adding fenugreek to both foods significantly reduced the IAUC compared to the food alone: white bread and jam, 180 ± 22 versus 271 ± 23 mmol × min/L (P = 0.001); fried rice, 176 ± 20 versus 249 ± 25 mmol × min/L (P = 0.001). Fenugreek also significantly reduced the area under the satiety curve for white bread with jam (134 ± 27 versus 232 ± 33 mm × hr, P = 0.01) and fried rice (280 ± 37 versus 379 ± 36 mm × hr, P = 0.01). It is concluded that fenugreek significantly decreased the PPG response and increased satiety among overweight and obese individuals.